Gerhard Herzberg : an illustrious life in science - Stoicheff, B. P. (Boris P.) (NRC Press ; McGill-Queens University Press, 2002)
Gerhard Herzberg (1904-1999) was one of the greatest scientists of the last century. Born and educated in Germany, he started his research just as the exciting discovery of quantum mechanics began unraveling the mysteries of the microscopic world. Herzberg chose to study spectroscopy, the light emitted and absorbed by atoms and molecules, which has played a central role in the development of modern science.